(untitled) (London Journal of Medical and Health Research, 2023)
In this research , we are going to deal with the probable mechanism behind the loculated pleural effusions using the Law of Viscous fluids against rough surfaces/walls. The idea of the research is to form a firm ground regarding the mechanism of pleural effusion.